2010
DOI: 10.1007/s00726-010-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

Apelin suppresses apoptosis of human vascular smooth muscle cells via APJ/PI3-K/Akt signaling pathways

Abstract: Apoptosis of vascular smooth muscle cells (VSMCs) plays an important role in regulating vascular remodeling during cardiovascular diseases. Apelin is the endogenous ligand for the G-protein-coupled receptor APJ and plays an important role in the cardiovascular system. However, the mechanisms of apelin on apoptosis of VSMCs have not been elucidated. Using a culture of human VSMCs as a model for the study of apoptosis, the relationship between apelin and apoptosis of human VSMCs and the signal pathway involved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 45 publications
3
59
0
2
Order By: Relevance
“…Additionally, apelin activates Akt in rat hippocampal neuronal cultures, suggesting a neuroprotective role (O'Donnell et al 2007), while in mouse cortical neurones, the neuroprotective action of apelin is blocked by the PI3K inhibitor wortmannin, implicating the PI3K/Akt pathway in this process (Zeng et al 2010). APJ signalling via PI3K/Akt is also involved in proliferation and anti-apoptotic actions in rat and human VSMCs respectively (Cui et al 2010, Liu et al 2010. Studies carried out in vivo have shown the involvement of apelin in cardioprotection via Aktmediated signalling ); however, the protective effect of apelin in ischaemia/reperfusion may be independent of Akt signalling (Kleinz & Baxter 2008).…”
Section: Apelin and The Pi3k/akt Pathwaymentioning
confidence: 99%
“…Additionally, apelin activates Akt in rat hippocampal neuronal cultures, suggesting a neuroprotective role (O'Donnell et al 2007), while in mouse cortical neurones, the neuroprotective action of apelin is blocked by the PI3K inhibitor wortmannin, implicating the PI3K/Akt pathway in this process (Zeng et al 2010). APJ signalling via PI3K/Akt is also involved in proliferation and anti-apoptotic actions in rat and human VSMCs respectively (Cui et al 2010, Liu et al 2010. Studies carried out in vivo have shown the involvement of apelin in cardioprotection via Aktmediated signalling ); however, the protective effect of apelin in ischaemia/reperfusion may be independent of Akt signalling (Kleinz & Baxter 2008).…”
Section: Apelin and The Pi3k/akt Pathwaymentioning
confidence: 99%
“…It was also reported that apelin suppresses apoptosis of human and mouse osteoblasts, and the anti-apoptotic action is mediated via the APJ/PI-3 kinase/Akt signalling pathway [15,25]. Apelin also inhibited human vascular smooth muscle cells (VSMCs) apoptosis induced by serum deprivation and increased Bcl-2 protein expression, but decreased Bax protein expression [26]. Apelin also activated in VSMCs the extracellular signal-regulated protein kinase (ERK) and Akt (a downstream effector of phosphatidylinositol 3-kinase) [26].…”
Section: Discussionmentioning
confidence: 94%
“…insan dil kanseri hücreleri üzerinde yapmış oldukları bir başka çalışmada, apelinin hücre canlılığını arttırdığını rapor etmişlerdir [57]. Çeşitli hücre tipleri üzerinde yapılan araştırmalarda apelin sinyallerinin hücrelerde anti-apoptotik etkiye neden olduğu bildirilmiştir [58][59][60]. …”
Section: Discussionunclassified